2022
DOI: 10.3390/cells11040752
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Serum MiRNA-8074 as a Novel Prognostic Biomarker for Multiple Myeloma

Abstract: MiRNA-8074 is a molecule with the potential to regulate the expression of key genes related to the pathogenesis of multiple myeloma (MM), i.e., TP53, MYC, MAPK1, and KIAA. We analyzed the predictive and prognostic value of miRNA-8074 expression in MM patients. In total, 105 newly diagnosed MM patients treated with thalidomide (n = 27), bortezomib (n = 41) and bortezomib with thalidomide (n = 37) were studied. For miRNA analysis, the column method and the Real-Time PCR technique with specific TaqMan Fast Advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The obtained results showed that a high expression of miR-8074 was associated with a worse clinical outcome, more precisely with a higher risk of death (HR = 4.12, 95% CI: 2.20–7.70; p = 0.0009) and with a significant reduction of PFS. This renders miR-8074 a useful tool for predicting the prognosis for MM patients [ 112 ]. Another non-coding RNA associated with clinical outcomes is miR-137.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results showed that a high expression of miR-8074 was associated with a worse clinical outcome, more precisely with a higher risk of death (HR = 4.12, 95% CI: 2.20–7.70; p = 0.0009) and with a significant reduction of PFS. This renders miR-8074 a useful tool for predicting the prognosis for MM patients [ 112 ]. Another non-coding RNA associated with clinical outcomes is miR-137.…”
Section: Discussionmentioning
confidence: 99%
“…More than 3.95% of total methylated DNA correlates with better OS. Szudy-Szczyrek et al [112] The high expression of miR-8074 is associated with a higher risk of death and shorter PFS in MM exposed to BTZ and THD. San-Miguel et al [113,114];…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of overexpression of this miRNA for shorter PFS and OS was also confirmed (respectively: HR = 2.28, 95%CI = 1.07–4.91; HR = 3.97, 95%CI = 1.32–11.90). Additionally, the authors noticed a positive correlation between miR-8074 and MYC expression (rho = 0.476), which may explain the role of this miRNA in the development of MM [ 54 ]. The MYC gene has a confirmed role in the pathogenesis of MM by intensifying cell proliferation and migration (Notch and Wnt signaling pathways) and stimulating angiogenesis (via VEGF), and its increased activity is associated with tumor progression and occurs in up to 60% of disease cases [ 55 ].…”
Section: The Role Of Mirna Expression In Diagnosis and Prognosis Of MMmentioning
confidence: 99%
“…miRNA is a short (about 22 nucleotides long) non-coding RNA fragment with the ability to regulate gene expression at the post-transcriptional level [7] . It is involved in the occurrence and development of tumors.…”
Section: Micro-ribonucleic Acid (Mirna) 231 Micro-ribonucleic Acid (M...mentioning
confidence: 99%